Genectic control of seed longevity in soybeans - Kueneman, E.A. (1983)
Soybean [Glycine max (L.) Merr.] seeds have a short storage life, especially in humid, tropical environments. However, a few varieties have been identified recently that have superior seed longevity. The purpose of this study was to determine if seed longevity is under maternal plant influence as is the case with many seed characteristics.